Integration Of Islamic Values In Mathematics Learning In Class IV Students Of Madrasah Ibtidaiyah - Indri Mahmudah; Muqowim Muqowim (Al-Madrasah: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Mathematics learning must experience changes in the context of improving the quality of religious education so it is necessary to add Islamic values that can increase optimal learning processes. The purpose of this study was to find out how to integrate Islamic values in learning mathematics in fourth-grade students of Madrasah Ibtidaiyah. This research is a qualitative research study of literature that is intended to describe the integration model of mathematics with Islamic values in learning mathematics. The data collection method is done by interview and literature review. The results of the study indicate several things are underlined in applying Islamic values and technology in learning mathematics. The findings related to this phenomenon, namely: 1) The IVG homeroom teacher at MI Aliyah 2 studied had implemented the integration of Islamic science values with mathematics in learning; (2) Teachers who apply the integration of mathematics with Islamic science adjust to the material being studied; (3) The advantages of integrating Islamic values in the mathematics learning system can instill honesty, discipline, and responsibility. Based on this statement the integration of mathematical concepts with Islamic values is very important to be applied as a way of forming the character of the nation's generation. Thus, it is necessary to develop a continuous analysis of mathematical material by linking the verses of the Qur'an which is the source of all sources of knowledge that can be taken wisdom and lessons through mathematics by every human being.